Implementing Spanlastics for Improving the Ocular Delivery of Clotrimazole: In vitro Characterization, Ex vivo Permeability, Microbiological Assessment and In vivo Safety Study - Abdelbari MA (Dove Medical Press, 2021)
Manar Adel Abdelbari,1 Shereen Sameh El-mancy,1 Ahmed Hassen Elshafeey,2 Aly Ahmed Abdelbary2,3 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, October 6 University, Giza, Egypt; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 3School of Life and Medical Sciences, University of Hertfordshire Hosted by Global Academic Foundation, Cairo, EgyptCorrespondence: Aly Ahmed AbdelbaryDepartment of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Kasr El-Aini, Cairo, 11562, EgyptTel +20 1149005526Email aly.abdelbary@pharma.cu.edu.egPurpose: The aim of this study was to encapsulate clotrimazole (CLT), an antifungal drug with poor water solubility characteristics, into spanlastics (SPs) to provide a controlled ocular delivery of the drug.Methods: Span 60 was used in the formulation of SPs with Tween 80, Pluronic F127, or Kolliphor RH40 as an edge activator (EA). The presence of EA offers more elasticity to the membrane of the vesicles which is expected to increase the corneal permeation of CLT. SPs were prepared using ethanol injection method applying 32 complete factorial design to study the effect of formulation variables (ratio of Span 60: EA (w/w) and type of EA) on SPs characteristics (encapsulation efficiency percent (EE%), average vesicle size (VS), polydispersity index (PDI) and zeta potential (ZP)). Design-Expert software was used to determine the optimum formulation for further investigations.Results: The optimum formulation determined was S1, which contains 20 mg of Tween 80 used as an EA and 80 mg of Span 60. S1 exhibited EE% = 66.54 ± 7.57%, VS = 206.20 ± 4.95 nm, PDI = 0.39 ± 0.00 and ZP = − 29.60 ± 0.99 mV. S1 showed highly elastic sphere-shaped vesicles. Furthermore, S1 displayed a sustained release profile and a higher ex vivo permeation across rabbit cornea relative to CLT suspension. Also, S1 revealed superior inhibition of Candida albicans development compared to CLT suspension applying 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) reduction technique. Moreover, in vivo histopathological examination assured the safety of S1 after ophthalmic application in mature male albino rabbits.Conclusion: Overall, the outcomes revealed the marked efficacy of SPs for ocular delivery of CLT.Keywords: clotrimazole, spanlastics, edge activators, XTT reduction technique, ocular drug delivery